Mental Toughness: A Gender-Based Descriptive Study of Pencak Silat Athletes on the West Java XV PORPROV Team of Subang Regency - Wahyu Saputra; Asep Akbaruddin (STKIP Pasundan, 2026)
This study aimed to describe the level of mental toughness among pencak silat athletes on the West Java XV PORPROV team of Subang Regency. The study employed a descriptive quantitative approach using a survey method. The participants were 15 athletes, and instrument used was a 23-item mental toughness questionnaire covering four components: thrive through challenge, sport awareness, tough attitude, and desire success. The results showed that the athletes’ overall mental toughness score had a mean of 67.00 with a standard deviation of 8.86, a minimum score of 56, and a maximum score of 81. Based on the mean ± 1 SD categorization, 2 athletes (13.3%) were in the low category, 9 athletes (60.0%) were in the moderate category, and 4 athletes (26.7%) were in the high category. Overall, mental toughness of the pencak silat athletes on the West Java XV PORPROV team of Subang Regency was in the moderate category.